Synthesis and characteristic applications of silicon resins for the modifying agent in heat conduction. Issue 5 (March 2022) - Jeffrey Kuo, Chung-Feng; Ahmad, Naveed; Lin, Sheng-Yu; Dewangga, Garuda Raka Satria; Dong, Min-Yan
Heat energy retention and dissipation have become key points of global smart textiles in recent years. This study describes the designing of silicon resin by using a sol–gel process, which acts as the modifying agent for siloxane substrate. The modifying agent was effectively blocked by silicon resin mixed with the ethylene or aluminum bond group, to control the molecular weight. Advanced polymer chromatography confirmed that the number average molecular weight (Mn ) of silicon resin is 41, 301 g mol −1, the weight average molecular weight (Mw ) is 47, 982 g mol −1, and the molecular weight distribution is 1.1617, which is relatively narrow. When the addition of vinyl groups is 5%, the silicone resin Mn decreases to 18, 906 g mol −1 and Mw decreases to 28, 641 g mol −1 . When the addition of aluminum bond groups is 5%, the silicone resin Mn decreases to 17, 497 g mol −1 and Mw decreases to 27, 114 g mol −1 . The result of thermogravimetric analysis shows that the pyrolysis temperature rises from 265.43°C to 266.17°C after the ethylene is added to the silicon resin, and the index of heat tolerance increases from 179.14°C to 191.38°C. After the addition of aluminum bond groups, the pyrolysis temperature rises from 265.43°C to 309.37°C, and the index of heat tolerance increases from 179.14°C to 193.09°C, meaning the silicone resin has higher thermal stability.